Dipteryx alata seedlings nutritional status in a recovery area in the Brazilian Savannah - Boni, Thaís Soto [UNESP]; Maltoni, Kátia Luciene [UNESP]; da Silva Mizobata, Kellian Kenji Gonzaga [UNESP] (FapUNIFESP (SciELO), 2020)
Dipteryx alata is an arboreal species found in the Brazilian Savannah (BS), that has potential human and animal uses, including nutrition, medicine, and revegetation. This study aimed to evaluate the nutritional status and growth of D. alata seedlings used to recover degraded soils to which residues had been added compared to seedlings grown in the BS. The degraded soil was treated with organic and agroindustrial residues. Twelve months after seedlings were introduced, they were evaluated for height, stem diameter, chlorophyll index, and concentration of foliar macro and micronutrients. The foliar concentration was determined for D. alata seedlings grown in the degraded area and BS. The addition of residues increased foliar concentration of seedlings grown in the degraded area; however, concentrations did not reach similar levels to seedlings grown in BS. D. alata accumulated Mn in plants. The height and stem diameter of seedlings responded positively to residue application.
Keywords: Ash from sugarcane bagasse; Degraded soil; Macrophytes; Residue